Orchid Root Associated Bacteria: Linchpins or Accessories? - Kaur, Jaspreet; Sharma, Jyotsna (Frontiers in Plant Science, 2021)
Besides the plant-fungus symbiosis in Arbuscular Mycorrhizal (AM) and Ectomycorrhizal (EM) plants, many endorhizal and rhizosphere bacteria (Root Associated Bacteria, or RAB) also enhance plant fitness, diversity, and coexistence among plants via bi- or tripartite interactions with plant hosts and mycorrhizal fungi. Assuming that bacterial associations are just as important for the obligate mycorrhizal plant family Orchidaceae, surprisingly little is known about the RAB associated with orchids. Herein, we first present the current, underwhelming state of RAB research including their interactions with fungi and the influence of holobionts on plant fitness. We then delineate the need for novel investigations specifically in orchid RAB ecology, and sketch out questions and hypotheses which, when addressed, will advance plant-microbial ecology. We specifically discuss the potential effects of beneficial RAB on orchids as: 1) Plant Growth Promoting Rhizobacteria (PGPR), 2) Mycorrhization Helper Bacteria (MHB), and 3) constituents of an orchid holobiont. We further posit that a hologenomic view should be considered as a framework for addressing co-evolution of the plant host, their obligate Orchid Mycorrhizal Fungi (OMF), and orchid RAB. We conclude by discussing implications of the suggested research for conservation of orchids, their microbial partners, and their collective habitats.